Identifikasi Virus Yang Berasosiasi Dengan Penyakit Mosaik, Kuning, Dan Klorosis Pada Tanaman Cabai Rawit (Capsicum Frutescens L.) - I GUSTI NGURAH BAGUS PRANATA PUTRA; NI MADE PUSPAWATI; I DEWA NYOMAN NYANA; I KETUT SIADI; GEDE SUASTIKA (Program Studi Agroekoteknologi, Fakultas Pertanian, Universitas Udayana, 2015)
ABSTRACT Identification of virus that associated with Mosaic, Yellow, and Chlorosis disease on Chili Pepper (Capsicum frutescens L) This study aims to identify the types of viruses associated with mosaic, yellow, and chlorosis that infect the plants of chili pepper ( Capsicum frutescens L. ) in Kerta village, Gianyar. The method used is the ELISA (Enzyme Linked Immunosorbent Assay) and molecular techniques through PCR (Polymerase Chain Reaction). Research activities include (1) Survey endemic locations of viral diseases in Kerta village, Gianyar (2) Collecting leaf of chilli peper that shown, mosaic, yellowing and chlorosis (3) serology test by ELISA (4) molecular detection through PCR. The results show the percentage average of pepper plants showing mosaic symptoms (52.13%), yellow (22.75%), chlorosis (5.45%) and healthy plant (19.67%). Serology test by ELISA technique showed that the mosaic disease induced by the triple virus that is TMV, ChiVMV, and CMV, whereas yellow symptoms infected by PepYLCV and chlorosis symptoms, infected by Polerovirus. RT-PCR technique successfully amplify the target DNA fragment size of 650 bp for Polerovirus and PCR successfully amplified the target DNA fragment size of 700 bp for PepYLCV in accordance with the specific primers were used. Keywords : Chili pepper, mosaic , yellow, chlorosis